The molecular biological characteristics of Vibrio vulnificus isolated in Guangzhou - ZHANG Jing; CHEN Huiling; HE Peng; HOU Shuiping; BAI Zhijun; TAO Xia; WU Xinwei (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo investigate the molecular and biological characteristics of Vibrio vulnificus （V. vulnificus）isolated from Guangzhou.MethodsThirty-eight strains of V. vulnificus were collected from Guangzhou， and whole-genome sequences were obtained. The population structure of V. vulnificus was inferred by utilizing 50 publicly available genome sequences obtained from NCBI. FineSTRUCTURE software was employed for this analysis. Antibiotic resistance and virulence factors were identified using CARD， ResFinder， and VFDB databases.ResultsFour well-supported phylogenetic groups or lineages （L1-L4） were identified， and all genomes of the strains in Guangzhou were classified into L1 （47%） and L2 （53%）. The predominant ST were ST357， ST157， ST136， ST139， ST345， ST303， and so on， which showed regional aggregation. Multiple genome identification of V. vulnificus revealed 11 drug resistance genes： acrF， CRP， catB9， rpoC， ugd， and others. MCR genes related to polymyxin resistance were identified in V. vulnificus for the first time. The species also carries 23 virulence genes in five classes encoding flagellin， type Ⅱ secretory system protein， capsular polysaccharide， RtxA toxin， iron overload， and other virulence-related genes.ConclusionVibrio vulnificus in Guangzhou undergoes highly homologous recombination and carries a variety of antimicrobial resistance genes and virulence-related genes. Therefore， monitoring and management of Vibrio vulnificus should be strengthened.